Correlation between different methods of assessing bone maturation - Souza, Daniela Correia Cavalcante; Nóbrega, Marina Tavares Costa; Pires, Andressa Cavalcanti; Lacerda, Rosa Helena Wanderley (Revista de Ciências Médicas e Biológicas, 2021)
Introduction: the skeletal maturity of na individual can be evaluated through different methods and it is an important tool to the diagnostic and treatment in othodontics. Objective: to verify the correlation between different methods of assessing bone maturation: Carpal Maturation Index (CMI), Cervical Vertebrae Maturation Stages (CVM) and Dental Mineralization Stages (DM). Methodology: the sample consisted of digitalized images of cephalometric, panoramic and hand and wrist radiographs of 73 patients. 50 were selected for analysis. Two examiners were properly calibrated, through images analysis from another database. Inter and intraexaminer reliability was measured by Kappa coefficient. The images were assessed according to Fishman (1982), Baccetti, Franchi and McNamara Junior (2002) and Nolla (1960) methods. All images were coded and data of all analyzes was transferred to spreadsheets. The data was processed in Matlab program for Windows, version 7.10.0, and analyzed using descriptive and inferential statistics. Results: the results demonstrated a positive correlation among bone maturity methods (CMI, CVM and DM), as well as between those methods and chronological age. Females showed precocity in reaching the stages of skeletal maturation indicators and CVM compared to males. It was observed that there was a correspondence between maturation methods for both genders. Conclusion: there was a correlation between skeletal maturation assessment methods and dental mineralization in patients. Significant differences were observed between genders for skeletal maturity assessment methods. There was a relation between the methods used for skeletal maturation and dental mineralization, as well as chronological age.